LIL3, a Light-Harvesting Complex Protein, Links Terpenoid and Tetrapyrrole Biosynthesis in Arabidopsis thaliana . Issue 2 (21st April 2017) - Hey, Daniel; Rothbart, Maxi; Herbst, Josephine; Wang, Peng; Müller, Jakob; Wittmann, Daniel; Gruhl, Kirsten; Grimm, Bernhard
Abstract : LIL3 associates with POR and CHLP and thus contributes to the supply of the two metabolites, chlorophyllide and phytyl pyrophosphate, required for the final step in chlorophyll a synthesis in Arabidopsis. Abstract: The LIL3 protein of Arabidopsis ( Arabidopsis thaliana ) belongs to the light-harvesting complex (LHC) protein family, which also includes the light-harvesting chlorophyll-binding proteins of photosystems I and II, the early-light-inducible proteins, PsbS involved in nonphotochemical quenching, and the one-helix proteins and their cyanobacterial homologs designated high-light-inducible proteins. Each member of this family is characterized by one or two LHC transmembrane domains (referred to as the LHC motif) to which potential functions such as chlorophyll binding, protein interaction, and integration of interacting partners into the plastid membranes have been attributed. Initially, LIL3 was shown to interact with geranylgeranyl reductase (CHLP), an enzyme of terpene biosynthesis that supplies the hydrocarbon chain for chlorophyll and tocopherol. Here, we show another function of LIL3 for the stability of protochlorophyllide oxidoreductase (POR). Multiple protein-protein interaction analyses suggest the direct physical interaction of LIL3 with POR but not with chlorophyll synthase. Consistently, LIL3-deficient plants exhibit substantial loss of POR as well as CHLP, which is not due to defective transcription of the POR and CHLP genes but to the posttranslational modification of their protein products. Interestingly, in vitro biochemical analyses provide novel evidence that LIL3 shows high binding affinity to protochlorophyllide, the substrate of POR. Taken together, this study suggests a critical role for LIL3 in the organization of later steps in chlorophyll biosynthesis. We suggest that LIL3 associates with POR and CHLP and thus contributes to the supply of the two metabolites, chlorophyllide and phytyl pyrophosphate, required for the final step in chlorophyll a synthesis.